Early deglaciation and paleolake history of Rio Cisnes Glacier, Patagonian Ice Sheet (44°S) - Garcia, Juan-Luis; Maldonado, Antonio; de Porras, Maria Eugenia; Delaunay, Amalia Nuevo; Reyes, Omar; Ebensperger, Claudia A.; Binnie, Steven A.; Luethgens, Christopher; Mendez, Cesar (My University, 2019)
The timing, structure, and landscape change during the Patagonian Ice Sheet deglaciation remains unresolved. In this article, we provide a geomorphic, stratigraphic, and geochronological deglacial record of Rio Cisnes Glacier at 44 degrees S and also from the nearby Rio Nirehuao and Rio El Toqui valleys (45 degrees S) in Chilean Patagonia. Our C-14, Be-10, and optically stimulated luminescence data indicate that after the last glacial maximum, Rio Cisnes Glacier experienced 100 km deglaciation between >19.0 and 12.3 ka, accompanied by the formation of large glacial paleolakes. Deglaciation was interrupted by several ice readvances, and by 16.9 +/- 0.3 ka, Rio Cisnes Glacier extended only 40% of its full glacial extent. The deglaciation of Rio Cisnes Glacier and other sensitive Patagonian glaciers occurred at least 1 ka earlier than the ca. 17.8 ka normally assumed for the local termination, coincident with West Antarctic isotope records. This early deglaciation can be linked to an orbital forcing-driven decline of Southern Ocean sea ice associated with a distinct atmospheric warming that is apparent for West Antarctica through Patagonia.
Keywords: last termination; last glacial-interglacial transition; last deglaciation; patagonia; patagonian ice sheet; paleolakes; glacial geomorphology; be-10 dating; osl dating; c-14 dating